A arquitetura modernista nas residências de Maringá : apropriações culturais (1950-1970) - Delmonico, Renato (2010)
This thesis has as objective to study the Modern Movement in Architecture in Brazil, specifically in Maringa city. This work was concerned about an analysis of Brazilian architecture and the process of appropriation of modernist formal vocabulary, favored from culture clashes in a borderline zone, understanding this concept, not as a territorial boundary, but as a place of encounters, where different social contexts interact. The main point of this research was the residential architecture of Maringá from 1950's to 1970's, a period coinciding with the peak of Brazilian modernism. By understanding of the residences as historical sources, we seek to understand through the analysis of architectural designs, photographs, news of the day, interviews and other theoretical work on the subject, as this "new" architecture spread throughout the country, surpassing socioeconomic barriers and spreading out among various social segments. Anyway, we seek to grasp and to demonstrate that these modernist houses, even not entirely showing Modern principies, are the resuit of the appropriation of the population of Maringa for a new constructive and cultural identity that symbolizes a passage in the history of the city.